Pengembangan Karakter Religius Siswa Melalui Sekolah Berbasis Pesantren Di Ma Ma’arif 7 Banjarwati Paciran Lamongan - Rokim, Rokim; Abdul Manan; Ayu Afita Sari (Akademika, 2024)
This research is entitled Development of Students' Religious Character through Pesantren-Based Schools at MA Ma'arif 7 Banjarwati Paciran Lamongan using qualitative methods. The purpose of this study is to determine the development of students' religious character through pesantren-based schools and find out the supporting and inhibiting factors in the development of religious character at MA Ma'arif 7 Banjarwati Paciran Lamongan. The result of this research is the development of religious character in MA Ma'arif 7 Banjarwati Paciran Lamongan carried out through various habituation activities applied by teachers to their students. Some of these activities are: habituation of morning ceremonies and joint prayers; habituation of congregational dhuhur prayers; and celebrating the commemoration of Islamic holidays. Teachers emphasize an attitude of gratitude and sincerity through the advice given. Teachers exemplify respectful attitudes towards parents and teachers. Teachers provide stories of inspirational figures, The teacher gives punishment to read Surah Al-Mulk and Al-Waqi'ah for students who are late for the morning ceremony; the teacher gives scholarships to students and students who memorize the Qur'an; the teacher invites students to perform qiyamul lail; the teacher lives in harmony and helps each other. Supporting and inhibiting factors in the development of students' religious character through pesantren-based schools are grouped into two categories: internal and external factors. Internal factors include customs, will, and heredity, while external factors include education and the environment.